PERBANDINGAN EFEKTIVITAS LAMA WAKTU RENDAM KAKI AIR HANGAT CAMPUR SERAI DAN GARAM PADA LANSIA HIPERTENSI - Aldo, Aldo; E.M. Gaghauna, Eirene; Santoso, Bagus Rahmat (Coping: Community of Publishing in Nursing; Vol 12 No 2 (2024): April 2024DO - 10.24843/coping.2024.v12.i02.p08, 2024)
Hypertension is a disease of the heart and blood vessels characterized by increased blood pressure. Non-pharmacological efforts can be done by soaking the feet in warm water which can have a relaxing effect and dilate blood vessels. The aim of this study was to compare soaking feet in warm water mixed with lemongrass and salt for 10 and 15 minutes in hypertensive elderly at the Cempaka Putih Community Health Center. The research method uses an experimental two group pretest posttest design. Purposive sampling with inclusion and exclusion criteria. Each group consisted of 19 respondents, tested using Mann Whitney. The results showed that the systolic pre-mean for the 10 minute group was 147,37 mmHg, and the diastolic average was 92,37 mmHg. The experimental group's 15-minute pre-systolic mean was 150,53 mmHg, with diastolic 88,42 mmHg. Post mean systolic results for the 10 minute group were 129,47 mmHg with diastolic 83,16 mmHg. In the experimental group 15 minutes post the mean systolic was 123,68 mmHg and diastolic 81,58 mmHg. The Mann Whitney test shows that there is a difference in the mean reduction in systolic and diastolic blood pressure with a p-value of 0,049 in systolic and 0,000 in diastolic.  The mean rank value shows a decrease in pre and post systolic at 10 minutes of 22,87 while at 15 minutes it is 16,13.  The results of the decrease in the mean diastole of the 15 minute group (11,23 mmHg) were smaller than those of 10 minutes (17,66 mmHg). It can be seen that the mean systole and diastole in the 15 minute group is smaller than 10 minutes, so it can be concluded that soaking the feet in warm water mixed with lemongrass and salt is more effective for 15 minutes in reducing both systolic and diastolic blood pressure in hypertensive elderly at the Cempaka Putih Community Health Center.